2015
DOI: 10.4161/15384047.2014.986973
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of biweekly vinorelbine and oxaliplatin in second- or third-line metastatic triple-negative breast cancer

Abstract: These authors contributed equally to this work.Keywords: chemotherapy, metastatic breast cancer, oxaliplatin, triple-negative, vinorelbineAbbreviations: TNBC, triple-negative breast cancer; mTNBC, metastatic triple-negative breast cancer; ER, estrogen receptor; PgR, progesterone receptor; HER2, human epidermal growth factor receptor 2; ORR, overall response rate; MBC, metastatic breast cancer; ECOG, Eastern Cooperative Oncology Group; TTP, time to progression; SD, stable disease; CBR, rate of clinical benefit;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
2
20
0
1
Order By: Relevance
“…In China, owing to changes in life styles and dietary structures, the morbidity of breast cancer is increasing rapidly and its age at onset is becoming increasingly younger (2,14). Due to rapid progress and the wide application of molecular biology, research on the pathogenesis of cancer and its therapy has made substantial achievements (15). Our results found that myricetin suppressed the cell viability of human breast cancer MCF-7 cells at least partly through the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 61%
“…In China, owing to changes in life styles and dietary structures, the morbidity of breast cancer is increasing rapidly and its age at onset is becoming increasingly younger (2,14). Due to rapid progress and the wide application of molecular biology, research on the pathogenesis of cancer and its therapy has made substantial achievements (15). Our results found that myricetin suppressed the cell viability of human breast cancer MCF-7 cells at least partly through the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 61%
“…While previous cohort studies [20][21][22], retrospective observations [23][24][25][26], and case reports [27,28] have addressed the clinical treatment of TNBC with apatinib or vinorelbine (Table 1), a randomized controlled clinical trial has not been reported in North China. As BRCA-positive patients would have poor responses to the therapeutic methods designed in this study, BRCA-negative female patients with locally recurrent or metastatic TNBC, who have previously received anthracycline and taxane treatment, will be the target population in this trial.…”
Section: Study Features and Objectivesmentioning
confidence: 99%
“…Currently, there are cohort studies [16][17][18], retrospective observations [19][20][21][22] and case reports [23,24] addressing the clinical treatment of TNBC with apatinib or vinorelbine ( Table 1). However, a randomized controlled clinical trial of apatinib combined with vinorelbine for TNBC has not been reported.…”
Section: Study Features and Objectivesmentioning
confidence: 99%